2013
DOI: 10.1152/ajpgi.00356.2012
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial transient receptor potential ankyrin 1 (TRPA1)-dependent adrenomedullin upregulates blood flow in rat small intestine

Abstract: . TU-100 contains multiple TRP activators. In the present study, therefore, we examined the involvement of TRP channels in the ADM-mediated vasodilatatory effect of TU-100. Rats were treated intraduodenally with the TRP vanilloid type 1 (TRPV1) agonist capsaicin (CAP), the TRP ankyrin 1 (TRPA1) agonist allyl-isothiocyanate (AITC), or TU-100, and jejunum IBF was evaluated using laser-Doppler blood flowmetry. All three compounds resulted in vasodilatation, and the vasodilatory effect of TU-100 was abolished by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 57 publications
(49 reference statements)
4
85
0
Order By: Relevance
“…Reactive oxygen species, including H 2 O 2, are known to be upregulated in colorectal mucosa biopsies of active IBD patients and in TNBS‐induced rat colons . The infiltration of white blood cells or the presence of oxidative stress will cause the production of H 2 O 2 in mucosa and submucosa at an early stage of the TNBS model . Our data were consistent with these findings; we found that the content of H 2 O 2 increased 2.68‐fold in TNBS rats compared with the control rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Reactive oxygen species, including H 2 O 2, are known to be upregulated in colorectal mucosa biopsies of active IBD patients and in TNBS‐induced rat colons . The infiltration of white blood cells or the presence of oxidative stress will cause the production of H 2 O 2 in mucosa and submucosa at an early stage of the TNBS model . Our data were consistent with these findings; we found that the content of H 2 O 2 increased 2.68‐fold in TNBS rats compared with the control rats.…”
Section: Discussionsupporting
confidence: 90%
“…Transient receptor potential ankyrin 1 has been suggested to be critical for visceral pain in IBD. TRPA1 is expressed abundantly in dorsal root ganglia (DRG) neurons innervating to the colon and on the epithelial cell of the intestine . TRPA1 was upregulated in the colon and DRG following experimental colitis .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was shown that the increased intestinal motility induced by Daikenchuto was inhibited by several serotonin receptor antagonists (Shibata et al, 1999;Satoh et al, 2001a,b). A recent study by Kono et al (2013) demonstrated that hydroxy-sanshools activate intestinal epithelial transient receptor potential cation channel, subfamily A, member 1 (TRPA1), which is highly expressed in enterochromaffin cells (serotonin-releasing cells), and may prove to be a novel target for constipation. In addition to the effects of these individual constituents, a recent study showed that Daikenchuto activates nicotinic acetylcholine receptors, which accounts for its effects on motility (Endo et al, 2014).…”
Section: Clinical Application and Pharmacology Of Kenchuto-based Jhmsmentioning
confidence: 99%
“…However, there are no previous reports of total and segmental transit analysis from the stomach to the anus using radiopaque markers after laparotomy. According to basic research on the use of DKT to regulate bowel activity [31,32], its action can be attributed to improvement in bowel blood flow, which in turn improves water absorption, and to protection against mucosal damage. Kono et al [33] found that DKT increased colonic vascular conductance, which was mainly mediated by calcitonin-gene-related peptide and its receptor components.…”
Section: Discussionmentioning
confidence: 99%